Modelling the long-term impacts of atmospheric pollution deposition and repeated forestry cycles on stream water chemistry for a holm oak forest in northeastern (Journal of Hydrology, 1995)
Estimates based on the MAGIC model of the long-term effects on stream water quality of forest management cycles as well as of atmospheric pollutant inputs for a holm oak catchment in northeastern Spain, show that despite high pollutant sulphur inputs as well as substantial base cation loss from the catchment owing to forest harvesting, stream water has not deteriorated in any major way. Acidification of the catchment will continue, to a limited degree, unless either sulphur deposition is reduced by more than 60% or forest harvesting schemes are terminated. The detrimental changes in water quality owing to acid deposition and forestry harvesting practice in other parts of Europe are not observed in this region, because of high base inputs from the atmosphere and high base cation weathering rates within the catchment.